Sanksi Pidana bagi Pelaku Tindak Kecurangan dalam Perekrutan Calon Pegawai Negeri Sipil di Indonesia - Anom Bagus Sanjaya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
The recruitment process for prospective civil servants in Indonesia is indeed very vulnerable to bribery, such as evidence of the problem of transparency in CPNS recruitment with cases of collusion involving government officials of the State Civil Apparatus who are proven to have accepted bribes and assisted prospective civil servants in a fraudulent manner. and causing a criminal act can be dismissed from his position, in accordance with Law Number 5 of 2014 concerning State Civil Apparatus. The formulation of the problem in this study are: 1) What is the arrangement for CPNS recruitment in Indonesia? 2) What are the criminal sanctions against perpetrators of fraudulent CPNS recruitment? The research method used is normative research with a statutory approach. Sanctions imposed on perpetrators of fraud are divided into two, namely administrative sanctions in the form of blacklist sanctions from the State Civil Service Agency which results in the perpetrators not being able to register to take the CPNS test for the rest of their life, Criminal sanctions imposed namely Law Number 11 of 2008 concerning Information and Transactions Electronic.